Tracking Performance Studies for Future Circular Collider (FCCee) with CLD Detector - Sadowski Gaelle; Andrea Jeremy; Besson Auguste; El Bitar Ziad (EPJ Web of Conferences)
The Future Circular Collider electron-positron (FCCee) feasibility study involves assessing the capabilities and performances of potential detector configurations. This study focuses on the impact of various detector parameters on tracking performances. Specifically, the influence of different geometries, material budgets, and magnetic field strengths on the precision and efficiency of tracking performance within the CLIC-Like Detector is investigated. Tracking performance is evaluated using full simulations. This study provides valuable insights into optimising the design parameters of the FCCee detector to achieve high tracking performance, contributing essential information for the ongoing FCCee feasibility study and future collider detector development.